The second season of excavations at Jebel Moya (south-central Sudan). (November 2020) - Brass, Michael; Adam, Ahmed; Vella Gregory, Isabelle; Abdallah, Rayan; Alawad, Osman; Abdalla, Ammar; Kozieradzka-Ogunmakin, Iwona; Wellings, Joss; Albadwi, Anfal; Moyne, Charles Le; Hassan, Fakri; Abdelrahman, Ali
Abstract: This report presents the latest data from ongoing excavations at Jebel Moya, Sudan. This year saw the opening of five new trenches and continued excavation of an archaeologically rich trench. We have recovered four individual burials, a mud brick wall and a number of animal and archaeobotanical remains. The excavations also yielded a longer pottery sequence, showing clearly that the site was in use by at least the sixth millennium BC. This season confirms the long and complex history of Jebel Moya and provides the material for future studies on population health and subsistence. This season also saw an increase in community engagement and a more detailed study of the various historical trajectories that make up the biography of Jebel Moya.